PENYULUHAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) SERTA PENCEGAHAN STUNTING DI DESA NANGTANG KECAMATAN CIGALONTANG - Taufik Hidayat Hidayat; Resha Resnawati Saleha; Ira Rahmiyani; Nike Widya Gantika Putri; Sedin Renaldi; Anindia Nuralifanisa; Ai Putri Lestari (Universitas Bakti Tunas Husada, 2022)
Clean and Healthy Living Behavior (PHBS) is a form of effort to provide lessons in the form of experience to each individual, family member, and the general public. The majority of the Nangtang Village community in stilt houses do not have private latrines, so they are accustomed to using public latrines made of bamboo (latrine) while poor sanitation and hygiene levels can increase the risk of stunting in children by 3 times. The purpose of this community service activity is to improve the Nangtang Village community regarding PHBS and stunting prevention. The community service method used is lectures and giving questionnaires in the form of pre-test and post-test. The result of the activity is the influence on the understanding of the material received based on age and level of education